Students’ Cognitive Load in Understanding Linear Equation in One Variable - Rofiq, Ainur; Sudirman, Sudirman; Muksar, Makbul (Universitas Muhammadiyah Mataram, 2026)
Cognitive load is the mental effort made by students in their working memory to process information received. This study aims to describe the cognitive load of students in understanding linear equation in one variable material. The research method used is qualitative with a case study type of research. The research was conducted at a junior high school in Malang. The research subjects were two active students selected based on the recommendation of the mathematics teacher in the class. Data were collected through observation sheets, interviews, and student reflection sheets, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that students experienced intrinsic, extraneous, and germane cognitive load. Intrinsic cognitive load occurred when faced with complex problems and story problems that required the processing of several concepts at once, such as equations, integer operations, distributive properties, and algebraic operations. Students experienced extraneous cognitive load because they did not have sufficient prerequisite knowledge due to the teacher providing apersepsi that did not help activate students' prior knowledge. Students misunderstood the definition of a linear equation in one variable and only memorized the rules for moving terms because the teacher used inappropriate terms in their explanation. Students were confused in understanding simple example questions because the teacher explained too quickly without giving students time to understand. Students' attention was divided because the teacher gave examples in the workbook, while the steps to solve the problems were written on the board. Students were unable to complete the exercises because the teacher did not pay attention to their understanding. Germane cognitive load occurred because students' understanding was procedural. This was because the teacher's learning strategy did not support the formation of knowledge schemas. These findings have implications for teachers to design learning that takes into account students' working memory capacity.